2022
DOI: 10.1111/hae.14555
|View full text |Cite
|
Sign up to set email alerts
|

BAFF rs9514828 gene polymorphism and the risk of the development of inhibitors in children with severe haemophilia A

Abstract: Introduction: Haemophilia A (HA) is an x-linked recessive disease due to deficiency of coagulation factor VIII (FVIII). The development of neutralizing antibodies (inhibitors) against infused FVIII is a major concern. B cell activating factor (BAFF) has been implicated in several autoimmune diseases.Aim: We aimed to evaluate the possible association of BAFF rs9514828 gene polymorphism and the risk of the development of FVIII inhibitor in children with severe HA.Methods: This cohort study was carried out on 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The association of BAFF polymorphisms in the development of additional autoimmune diseases has been displayed previously [39][40][41][42][43][44][45][46][47]. BAFF rs9514828 polymorphism is found to be connected with numerous autoimmune and in ammatory disorders such as SS, lymphoma, leukemia, haemophilia and periodontitis through some scienti c investigations [48][49][50][51][52]. In an investigation by Nezos et al, [49] it was found that high risk pSS group was characterized by higher frequency of the minor T allele of the rs9514828 BAFF polymorphism compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of BAFF polymorphisms in the development of additional autoimmune diseases has been displayed previously [39][40][41][42][43][44][45][46][47]. BAFF rs9514828 polymorphism is found to be connected with numerous autoimmune and in ammatory disorders such as SS, lymphoma, leukemia, haemophilia and periodontitis through some scienti c investigations [48][49][50][51][52]. In an investigation by Nezos et al, [49] it was found that high risk pSS group was characterized by higher frequency of the minor T allele of the rs9514828 BAFF polymorphism compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The association of BAFF polymorphisms in the development of further autoimmune disorders has been revealed theretofore [39][40][41][42][43][44][45][46][47]. BAFF rs9514828 polymorphism is found to be linked to several in ammatory and autoimmune diseases via several scienti c studies [48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%